Glossophobia: Fear of Public Speaking Among Senior High School Students of Aliaga National High School - Tamayo, Vladimir T.; Caber, Jonalyn T. (International Journal of Humanities and Education Development (IJHED), 2022)
This study entitled “Glossophobia: Fear of Public Speaking Among Grade 11 Senior High School Students in Aliaga National High School” aimed to describe and analyze the components that contribute to the glossophobia among Grade 11 Senior High School students. Furthermore, it sought to determine the significant difference in the components to glossophobia among the students in terms of their profile. It also aimed to create interventions that can be applied to address challenges and issues on gloosophobia that the students encountered during public speaking class.